Clinical features and laboratory findings of dengue fever in German travellers: A single-centre, retrospective analysis. Issue 1 (January 2016) - Tavakolipoor, Pulad; Schmidt-Chanasit, Jonas; Burchard, Gerd Dieter; Jordan, Sabine
Summary: Background: Dengue fever (DF) is one of the most relevant human arboviral infections worldwide and has become a frequent cause of fever in the returning traveller. This retrospective study aimed to characterize epidemiological and clinical features and laboratory findings of dengue fever in German travellers. Methods: This descriptive study analyzed medical records of patients diagnosed with DF presenting at the Section of Tropical Medicine of the University Medical Centre Hamburg-Eppendorf from 2007 to 2011. Data were collected and analyzed retrospectively. Results: In total, data of 119 DF patients (52 female, 67 male) were included in this study. The median age of the patients was 35 (range 15–75 years). DF was most frequently acquired in South-East Asia (n = 65; 54.7%), and in particular in Thailand (n = 23; 19.7%). A considerable percentage of DF infections (n = 14; 11.8%) was imported from Africa. Patients predominantly presented with fever, headache, rash, myalgia and arthralgia but also with gastrointestinal symptoms, i.e. diarrhoea. Nine patients showed signs of minor haemorrhagic manifestations. Neurological complications occurred in 13 patients. Low platelet count, leukopenia and elevated liver enzymes were the most relevant laboratory findings. Twenty patients (17.8%) had to be hospitalized. Overall, the clinical course was mostly mild to moderate, 13 patients (10.9%) showed DF warnings signs, no fatalities occurred. Conclusions: DF presented as a mostly mild to moderate disease in this study cohort. Outpatient treatment was adequate for the majority of patients. Still, detailed knowledge of clinical symptoms and laboratory features is essential for appropriate triage.